Phytosynthesis and Antileishmanial Activity of Gold Nanoparticles by Maytenus Royleanus. Issue 4 (29th December 2015) - Ahmad, Aftab; Syed, Fatima; Imran, Muhammad; Khan, Arif Ullah; Tahir, Kamran; Khan, Zia Ul Haq; Yuan, Qipeng
Abstract: In this report, we present a simple and green approach to synthesize gold nanoparticles (AuNPs) with efficient antileishmanial activity. Phytochemicals from the aqueous extract Maytenus royleanus stem were used to reduce and stabilize the gold ions into metallic nanoparticles. UV‐Vis spectroscopy was employed to detect the characteristic surface plasmon resonance pattern of AuNPs (550 nm). X‐ray diffraction (XRD) and energy dispersive X‐ray studies were carried out to determine the crystalline nature and elemental composition of AuNPs. The surface functionalities of nanoparticles were identified with Fourier‐transform infrared spectroscopy. XRD and transmission electron microscopy revealed that AuNPs were mostly hexagonal in shape with an approximate particle size of 30 nm. Significant antileishmanial activity was shown by AuNPs. AuNPs inhibited the parasite growth by 75% after 72 h of incubation. The findings of this study indicate that these nanoparticles could be an alternative, safe, and effective source of antileishmanial agents. Practical Applications: Maytenus royleanus is widely used in folk medicine for various types of ailments however; this specie has not been analyzed for various biological activities. Furthermore, no report is available on the synthesis and biological activities of gold nanoparticles from Maytenus roylenus . Metal nanoparticles are extensively used in products such as detergents, soaps, shampoos, cosmetic products, toothpaste and pharmaceutical and medical area. The assessment of the antioxidant properties and leishmanicidal activity of gold nanoparticles from M. royleanus may give an insight into its applications in drug development.